Natural Defense Mechanisms of the Human Brain against Chronic Ischemia - A. V. Sergeev; S. S. Stepanov; V. A. Akulinin; A. V. Mytsik (Общая реаниматология)
Objective: to study the structural bases of natural defense mechanisms of the human brain against chronic ischemia. Materials and methods. To accomplish this, histological, immunohistochemical (NSE, calbindin, NPY, p38) and morphometric examinations of intraoperative biopsy specimens were performed to determine the reorganization of excitatory and inhibitory neurons in the ischemic penumbra of the temporal cerebral cortex (CC). Morphometric analysis was made using the specially developed algorithms to verify neurons and their elements in the ImageJ 1.46 program. Results. The reduction in the total numerical density of neurons and synapses in chronic ischemia was ascertained to be accompanied by the compensatorily enhanced expression of NSE, calbindin, p38, and NPY in the remaining CC neurons. There were signs of hypertrophy of inhibitory CC interneurons and growth of their processes. In consequence, the impact of inhibitory CC interneurons on excitatory neurons was likely to enhance. Conclusion. In chronic ischemia, the human brain is anticipated to respond to damage to some cells via compensatory excitatory and inhibitory neuronal reorganization directed towards its natural defense against excitatory damage and towards better conditions for compensatory recovery of the structure and function of CC.